Factors influencing the development of pre-service science teachers’ technological pedagogical content knowledge in a pedagogical makerspace - Max, Anna-Lisa; Weitzel, Holger; Lukas, Sarah (Frontiers in Education, 2023)
In an increasingly digitalized world, pre-service and in-service teachers need subject-specific didactic competencies to be able to plan their lessons appropriately and use their knowledge to promote digital competencies among students. Building on competency models such as the TPACK framework, this article explores the extent to which specific digital competencies relevant to preservice teachers can be developed through project work in a pedagogical makerspace and examines the extent to which contextual factors such as technological self-efficacy, motivation and technology acceptance influence the development of pre-service teachers' TPACK and their intention to use digital media. To this end, 495 pre-service science teachers from both intervention and control groups completed a pre-post digital questionnaire before and after the intervention. The data were used for structural equation modelling.The results show that the level of TPACK before the intervention is an important predictor of TPACK after project work. Furthermore, TPACK before the intervention positively influences preservice teachers' intention to use digital media in the future. Also, the perceived usefulness for professional use and the intention to use information and communication technologies (ICT) are strongly influenced by TPACK. Consequently, it appears significant to enable a low-threshold entry point at the beginning of the study to provide a solid foundation upon which more advanced TPACK can be built. Motivation and technology acceptance are strongly correlated. Therefore, teacher training should focus on motivation and acceptance of technology.